PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DENGAN MODEL FUZZY MODEL ATTRIBUTE DECISION MAKING (FMADM) PENILAIAN KINERJA KARYAWAN DTPEDULI - Fajar Agustini; Elien Riris Ariska (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2019)
Performance assessment of a job in an agency or company is a stage of job evaluation to determine the benchmark in determining the quality and achievement of each employee. In the process, even an agency or company has a standard to measure the success of work. With the many service programs and empowerment of the people conducted in DTPeduli Bekasi encourage each employee to provide the best performance of each employee. However, in the development of performance appraisal is done less than the maximum because there is no system support. Results from research Employee performance assessment on DTPeduli Bekasi with some aspects of the criteria using Fuzzy Simple Additive Weighting (FSAW) model has been running well and can generate weighting assessment criteria and information clear and fast compared to the calculation manually so that Branch Head DTPeduli Bekasi can use it as a tool for decision making appropriate in decision making employee performance appraisal in DTPeduli Bekasi.